The Implementation of Jugular Venous Pressure Assessment in The Intensive Care Unit Along Border Areas - Lesmana, Hendy; Yuliana, Yuliana; Aminuddin, Aminuddin (Poltekkes Kemenkes Palu, 2024)
This comparative study aimed to assess the utility of jugular venous pressure (JVP) measurements in evaluating changes in central venous pressure (CVP) among critically ill patients in resource-limited border area hospitals. The study included 100 patients admitted to the intensive care unit (ICU) with a central venous catheter inserted in the chest. JVP and CVP measurements were performed, and the data were analyzed using the Wilcoxon signed-rank test. The results revealed significant differences between direct CVP and JVP measurements. However, when the measurements were categorized into low, normal, and high ranges, a 98% concordance was observed between CVP and JVP values, with no significant differences noted. The findings suggest that JVP measurement is a reliable non-invasive method for assessing right atrial pressure and fluid volume status in ICU patients, particularly in resource-limited settings. Nurses working in border area hospitals with limited resources can benefit from categorizing JVP measurements as low, normal, or high to monitor patients' hemodynamic status effectively. The study highlights the importance of JVP measurement as a valuable tool for nurses in ICUs, general wards, and emergency departments to detect changes in CVP and monitor fluid volume status in critically ill patients.